Patient-reported symptoms are a more reliable predictor of the societal burden compared to established physician-reported activity indices in inflammatory bowel disease: a cross-sectional study - Decker, Barbora; Tuzil, Jan; Lukas, Milan; Cerna, Karin; Bortlik, Martin; Velackova, Barbora; Pilnackova, Barbora; Dolezal, Tomas (Expert review of gastroenterology & hepatology, 2023)
BACKGROUND: The societal burden of inflammatory bowel diseases (IBD) is not well documented, and further studies are needed to quantify the costs of the disease state. Thus, the aim was to estimate the societal burden and identify its predictors. METHODS: A cross-sectional questionnaire-based study complemented by objective data from patient medical records was performed for patients with Crohn's disease (CD) and ulcerative colitis (UC). RESULTS: We analyzed data from 161 patients (CD: 102, UC: 59). The overall work impairment reached 15.4%, 11.2% vs. 28.8% without/with self-reported symptoms (p = 0.006). Daily activity impairment was 19.3%, 14.1% vs. 35.6% (p < 0.001). The disability pension rate was 28%, 23% vs. 44% (p = 0.012). The total productivity loss due to absenteeism, presenteeism, and disability amounted to 7,673 €/patient/year, 6,018 vs. 12,354 €/patient/year (p = 0.000). Out-of-pocket costs amounted to 562 €/patient/year, 472 vs. 844 €/patient/year (p = 0.001). Self-reported symptoms were the strongest predictor of costs (p < 0.001). CONCLUSION: We found a high societal burden for IBD and a significant association between patient-reported disease symptoms and work disability, daily activity impairment, disability pensions, and out-of-pocket costs. Physician-reported disease activity is not a reliable predictor of costs except for out-of-pocket expenses.
Keywords: hodnocení výsledků péče pacientem; ulcerative colitis; Cross-Sectional Studies; Humans; idiopatické střevní záněty; Crohn’s disease; absenteeism; Colitis, Ulcerative; lidé; ulcerózní kolitida; productivity costs; Patient Reported Outcome Measures; Crohn Disease; průřezové studie; Crohnova nemoc; out-of-pocket costs; Inflammatory Bowel Diseases; presenteeism